Trait Forgiveness Moderated the Relationship Between Work Stress and Psychological Distress Among Final-Year Nursing Students: A Pilot Study - Li, Lingyan; Yao, Caixia; Zhang, Yan; Chen, Guangyuan (Frontiers in Psychology, 2020)
This study was to explore the potential moderating effect of trait forgiveness and its facets on the relationship between perceived work stress and psychological distress among Chinese nursing students in clinical practice. A total of 182 Chinese nursing students who had been receiving final-year clinical training completed self-report measures of nursing work stress, trait forgiveness and psychological distress. Correlation analysis and hierarchical multiple regressions were mainly applied for data analysis. Results showed that trait forgiveness was negatively associated with psychological distress, even after controlling for the effects of perceived work stress and demographic/workplace related variables. Further analyses indicated that the ability to forgiveness of situations was particularly crucial in reducing the negative effects of perceived work stress on psychological well-being, especially when students perceived higher level of stress. These results demonstrated that alternative interventions targeting on trait forgiveness, especially those programs which can improve one’s ability to acceptance uncontrollable bad circumstances, may be beneficial for the well-being of nursing students in clinical practice.